Adaptasi Sosial Mahasiswa Non-Muslim di Kampus Negeri Syariah - Sudarman, Sudarman; Baren, Maria; Husna, Cut Asmaul; Amri, Saiful (Journal of Administration, Governance, and Political Issues, 2025)
This study aims to determine the description of the abilities of male and female non-Muslim students during their education at Teuku Umar University, which is a Special Autonomous Region with a focus on implementing Islamic Sharia. The research method used is qualitative with 38 informants, consisting of 2 non Muslim students, 1 Muslim student who is a peer of the non-Muslim informant selected by purposive sampling, and 35 Muslim students selected by random sampling. The results of the study showed that there were no significant obstacles in the interaction and adaptation of non-Muslim students to the learning environment, although initially there was a feeling of discomfort, especially for non-Muslim female students when dealing with Muslim female students who wore headscarves or hijab. Islamic Sharia courses can be replaced with a certificate from the religious leader of the student concerned. The experience of culture shock experienced by non-Muslim students is considered a valuable experience. However, the limited understanding and views of each other's religion, culture, and customs require non-Muslim students to be more careful in mingling. This is sometimes considered by Muslim students as a form of self-exclusion and arrogance. Access to education is not limited; all students, both Muslim and non-Muslim, have the same rights. Regarding culture, there are differences that are felt as natural, despite protective efforts from Muslim student groups that sometimes seem discriminatory.In conclusion, despite religious and cultural differences, non-Muslim students are able to adapt well to the environment of Teuku Umar University which is based on Islamic Sharia, with equal rights and access, but it is necessary to increase interfaith understanding to reduce misunderstandings and exclusive attitudes.